The Catholic ethic in American society : an exploration of values - Tropman, John E. (San Francisco : Jossey-Bass, 1995)
Based on years of scholarly research, the Catholic Ethic in American Society reveals a Catholic ethic that parallels the more well-known Protestant ethic. Tropman presents an innovative analysis of the deeply ingrained attitudes Americans have about money and work and their view of people who have neither. In this book, Tropman offers a fresh perspective on the Protestant "achievement" ethic by contrasting it with the newly identified Catholic "sharing" ethic.
He outlines the key features that distinguish the Catholic ethic from its Protestant counterpart, including the perspectives of each ethic on the value of money and work, the importance of family and community, and the individual. The Protestant ethic - first articulated by sociologist Max Weber in the early 1900s - is rooted in the values of work, wealth, and achievement, whereas the Catholic ethic is firmly based on longstanding traditions and beliefs of sharing. Given the fundamental differences between the two ethics, the Catholic ethic has a stronger value base for providing assistance to others, especially the poor and the disadvantaged.
Because of the Protestant ethic's emphasis on achievement and self-reliance, charitable acts become fraught with concern, worry, and hesitancy. Distinguishing between the poor who are worthy and those deemed unworthy becomes an essential part of the helping activity.
. The Catholic Ethic in American Society is a valuable work for sociologists, political scientists, social activists, religion scholars and students, and fundraisers of Catholic charitable organizations.
Foreword / Rembert G. Weakland -- Introduction: Conflicting Values in American Society -- Pt. 1. The Protestant and Catholic Ethics in Context. 1. Religion as a Basis of Cultural Values: The Protestant and Catholic Ethics. 2. A Closer Look at the Protestant Ethic -- Pt. 2. Facets of the Catholic Ethic. 3. Attitudes Toward Work and Money. 4. An Emphasis on Family, Community, and Mercy. 5. This World and the Next in the Catholic Ethic -- Pt. 3. The Catholic Ethic and the Culture of Sharing. 6. The Tradition of Sharing. 7. The Institutional Church and Theology -- Pt. 4. The Catholic Ethic and Society. 8. Conceptions of Self and Society. 9. Looking Ahead.
Includes bibliographical references (p. 205-224) and index.
Keywords: Catholics -- United States -- Attitudes; Values -- United States; Christian sociology -- Catholic Church -- United States; Christian ethics -- Catholic authors; United States -- Church history -- 20th century